Climate event consequences on food insecurity and child stunting among smallholder farmers in Uganda: a cross-sectional study - Stephanie Ly; Patrick Olobo Okello; Robert Mpiira; Zulfigar Ali (Elsevier, 2018)
Background: Climate fluctuations and crop loss are predicted for Uganda. The rural poor rely on subsistence farming, and the consequences of climate events including droughts, floods, and pests have a considerable impact on food security and health. Nationally, 29% of Ugandan children are stunted or below expected height. In this study, we investigated farmers' experiences of climate events with household food insecurity and child stunting. Methods: BRAC Uganda did a cross-sectional study with random sampling across 210 villages in four districts in southwestern Uganda between October and December 2015. Questionnaires on socioeconomics, nutrition, and farming were administered to 7787 smallholder farmers. Anthropometry measurements were taken from the youngest child under 2 years in each household. Stunting, defined as a height-for-age Z-score below −2, was analysed using logistic regression. Food insecurity, self-reported as the number of months without enough food to meet needs, was analysed using multivariate linear regression. Findings: Most adults had received only primary-level education and mean monthly income was 332 274 Ugandan Shillings (US$92). In the past 12 months, 6815 (87·8%) farmers experienced a major loss of crops due to drought, 1595 (20·6%) due to flooding, and 7754 (39·1%) due to pests and disease. Food insecurity was reported in 7269 (93·3%) households, for a mean of 4·53 (SD 2·84) out of 12 months. Anthropometric data were collected from 2177 children with a mean age of 11·6 months. 899 were stunted (41·3%). Households with drought-related crop loss had higher odds of child stunting (OR 1·38, 95% CI 1·01-1·89) than households with no crop loss, after controlling for food insecurity, income, education, the child's sex, and age. Food insecurity was significantly associated with crop loss due to drought (p<0·001) and pests (p<0·001), after controlling for covariates. Interestingly, household coping behaviours after pest-related crop loss changed the pest loss effects, which suggests farmers could influence food insecurity. Interpretation: As climate patterns shift in Uganda, smallholder farmers will continue to experience events like drought, flooding, and pests. In our study, most farmers' food security was affected by drought and pests, and droughts were linked to child stunting. These findings have implications in building resiliency in crops and farmer techniques to mitigate climate shocks. Funding: BRAC, Japan Social Development Fund, World Bank Group Africa Gender Innovation Lab, UCLA World Policy Analysis Center, Conrad N Hilton Foundation, UCLA FSPH Dean's Global Health Fellowship.